2018
DOI: 10.5582/irdr.2018.01081
|View full text |Cite
|
Sign up to set email alerts
|

A catastrophic nightmare of the interventional cardiologist: Iatrogenic left main artery dissection and longitudinal stent deformation

Abstract: Iatrogenic left main coronary artery dissection is a rare but potentially life-threatening complication of invasive coronary procedures. The newer generation drug eluting stents have shown a greater safety and efficacy compared to first generation drug eluting stents. We report a 60-year-old woman with iatrogenic left main coronary artery dissection who failed bailout stenting and underwent coronary artery bypass grafting. The strategy for managing left main coronary artery dissection is variable and depends u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Especially in cases of very intense intracoronary calcification and severe atherosclerosis, or abnormal anatomic output of LMCA, LMCA dissections may occur due to subintimal passage of rigid and hydrophilic wires used during the procedure, inappropriate small diameter catheter selection, excessive manipulation of catheter, use of left amplatz and extra back up catheters and deep intubation of catheters, rapid and excessive contrast applications and operator-dependent reasons [3][4][5]. LMCA dissection management depends on the patient's clinical condition, the causative factor, antegrade flow and hemodynamic status and the character of the dissection line progression.…”
Section: Discussionmentioning
confidence: 99%
“…Especially in cases of very intense intracoronary calcification and severe atherosclerosis, or abnormal anatomic output of LMCA, LMCA dissections may occur due to subintimal passage of rigid and hydrophilic wires used during the procedure, inappropriate small diameter catheter selection, excessive manipulation of catheter, use of left amplatz and extra back up catheters and deep intubation of catheters, rapid and excessive contrast applications and operator-dependent reasons [3][4][5]. LMCA dissection management depends on the patient's clinical condition, the causative factor, antegrade flow and hemodynamic status and the character of the dissection line progression.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have suggested that there is instability of plaque and endothelial cell dysfunction in females associated with changes in estrogen and progesterone levels which in turn increases the stress of vessel walls and risk of dissection [18]. Vigorous injection of contrast, selection of larger catheters, inappropriate positioning of catheters, especially in patients with ostial lesions and subintimal passage of guidewire, are also associated with risk of CICD [19]. In our case, the patient presented with NSTEMI, was hemo-dynamically stable, had left main disease but no ostial lesion identified, and had a fixed defect on angiography and intravascular ultrasound without any distal propagation even with repeated contrast injections, therefore our patient had SCAD rather than CICD.…”
Section: Discussionmentioning
confidence: 99%
“…Our study was conducted based on previous studies and a review of LSD cases (Table 1 , Ref. [ 1 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]). Furthermore, we thoroughly examined the existing literature on LSD.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, other studies have reported that not all cases of LSD result in benign symptoms, with 14% of patients experiencing serious adverse events. These adverse events can include the need for heart bypass surgery due to the inability to remove the lodged medical device after LSD [ 8 ], acute stent thrombosis, subacute stent thrombosis, very late stent thrombosis [ 9 ], ISR, and death. Limited clinical studies have suggested that re-stenting or postdilatation management after the occurrence of LSD may reduce the incidence of adverse events associated with LSD.…”
Section: Literature Reviewmentioning
confidence: 99%